ChemInform Abstract: Asymmetric Hydrogenation of tert‐Alkyl Ketones: DMSO Effect in Unification of Stereoisomeric Ruthenium Complexes. Issue 3 (21st January 2014) - Yamamura, Tomoya; Nakatsuka, Hiroshi; Tanaka, Shinji; Kitamura, Masato
Abstract The asymmetric hydrogenation of functionalized tert‐alkyl ketones can be realized for the first time by using a binaphthalen derived Ru‐complex in combination with coordinated DMSO to yield chiral alcohols with high enantioselectivities.